HydroCoil for Endovascular Aneurysm Occlusion (HEAL) Study: 3–6 Month Angiographic Follow-Up Results - Cloft, H.J. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: The HydroCoil Embolic System (HES) was developed reduce recurrences of aneurysms relative to platinum coils. This study was conducted to evaluate the recurrence rate of cerebral aneurysms 3–6 months after treatment with HES.METHODS: We report the results in 135 cerebral aneurysms treated with HES in a prospective multicenter registry. Angiographic results 3–6 months after treatment were evaluated at a core laboratory. Wide variation in HES utilization within the HydroCoil for Endovascular Aneurysm Occlusion (HEAL) registry (HES representing 5% to 100% of the coil length used) allowed for subgroup analysis with regard to percentage length, last coil used, and packing attenuation in small (<10 mm) aneurysms.RESULTS: The overall recurrence rate was 38 (28.1%) of 135, which included a number of large, giant, and previously recurrent aneurysms. When HES represented ≥75% of coil length, the recurrence rate was 0 (0%) of 18, whereas with <75% length of HES, the recurrence rate was 16 (23%) of 71 (P = .035). When the final coil deposited was a HES coil, the recurrence rate was 6 (11%) of 53, whereas when the final coil was platinum, the recurrence rate was 10 (29%) of 34 (P = .047). When the packing attenuation was ≥50%, the recurrence rate was 11 (19%) of 59, whereas for packing attenuation <50%, the recurrence rate was 5 (18%) of 28. The packing attenuation calculations were very error-prone.CONCLUSION: Although the overall recurrence rates for small and large aneurysms in HEAL were no lower than published rates for aneurysms treated with platinum coils, patients treated in HEAL had a reduced recurrence rate when greater than 75% of the coil length used to treat an aneurysm was HES and when the final coil was HES.